2021
DOI: 10.3390/foods10071558
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Aronia, Red Ginseng, Shiitake Mushroom, and Nattokinase Mixture on Insulin Resistance in Prediabetic Adults: A Randomized, Double-Blinded, Placebo-Controlled Trial

Abstract: We determined whether oral consumption of Aronia, red ginseng, shiitake mushroom, and nattokinase mixture (3.4: 4.1: 2.4: 0.1 w/w; AGM) improved glucose metabolism and insulin resistance in prediabetic adults in a 12-week randomized, double-blinded clinical trial. Participants with fasting serum glucose concentrations of 100–140 mg/dL were recruited and randomly assigned to an AGM or placebo group. Participants of the AGM group (n = 40) were given an AGM granule containing 4 g of freeze-dried Aronia, red ginse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Thus, Aronia may be beneficial in persons with more severe or poorly controlled T2D, but no conclusions can be drawn due to the low number of studies. In addition, one RCT examining supplementation with a mixture of Aronia, red ginseng, shitake mushroom, and nattokinases in 40 prediabetic individuals found that this mixture compared to placebo had no impact on glucose levels during an oral glucose tolerance test but improved fasting insulin and HOMA-IR index [ 107 ]. However, this study does not clarify the impact of Aronia per se, and therefore, is not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Aronia may be beneficial in persons with more severe or poorly controlled T2D, but no conclusions can be drawn due to the low number of studies. In addition, one RCT examining supplementation with a mixture of Aronia, red ginseng, shitake mushroom, and nattokinases in 40 prediabetic individuals found that this mixture compared to placebo had no impact on glucose levels during an oral glucose tolerance test but improved fasting insulin and HOMA-IR index [ 107 ]. However, this study does not clarify the impact of Aronia per se, and therefore, is not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It also improves glucose metabolism in insulin-deficient type 2 diabetic rats by enhancing insulin secretion and reducing insulin resistance. 27,126 Li X used genetic engineering to clone long-acting glucagon-like peptide-1 (5 × GLP-1) and NK into E. coli by SOE PCR to obtain a fusion peptide with significant antithrombotic properties, resulting in fasting blood glucose levels similar to normal levels in experimental mice (Fig. 4).…”
Section: Prevention Of Hypertension and Hyperglycemiamentioning
confidence: 99%
“…Researchers have studied crude extracts of NK and have shown that NK can effectively prevent or treat blood clots through direct or indirect routes and intervene in diseases such as hypertension, hyperglycemia, and liver cancer. [24][25][26][27][28] In addition, NK-producing strains not only produce NK when acting on different substrates but also give different properties to fermented foods depending on the fermentation substrate, such as an improvement of antioxidant activity and absorbability, and the production of polyphenolic compounds. 22,29,30 Therefore, safe strains with the ability to produce NK can also potentially develop functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, 1236 RCTs were not relevant to the subject, leaving 202 records eligible for full-text review. Furthermore, after excluding 6 studies examining the impact of ginseng in combination with other ingredients due to the impossibility of determining the independent effect of ginseng [43][44][45][46][47][48], 3 eligible studies which reported in a language other than English [49][50][51], 1 study with multiple-crossover, acute dose escalation design [52], and 172 records which did not provide sufficient data and/or did not fulfill the inclusion criteria, 20 RCTs with 24 effect sizes met the inclusion criteria for qualitative synthesis.…”
Section: Study Selectionmentioning
confidence: 99%